Students’ High-Frequency Vocabulary Profile: A Corpus Study at Manado State Institute of Islamic Studies - Tahir, Muhammad Raihan Praba; Simbuka, Srifani; Kryati, Lies (Jurnal Ilmiah Iqra', 2025)
This research examines the high-frequency vocabulary knowledge of students at Manado State Institute of Islamic Studies utilizing a corpus-based approach. By applying quantitative research design and utilizing the AntWordProfiler software as the mean for generating statistical data of the vocabulary, the research identifies and analyzes the students’ lexical proficiency within the first and second General Service Lists (GSL). The results indicate that students demonstrated limited mastery of high-frequency words, covering only 18% of GSL 1 and 10% of GSL 2, with an overall inclusion of merely 15% across both lists. These findings highlight a critical gap in students' foundational English vocabulary, which has significant implications for English language teaching and curriculum development at the institution. To improve language acquisition outcomes, tailored vocabulary instruction strategies and curriculum adjustments are suggested to enhance students' mastery of high-frequency vocabulary.